Dietary water affects human skin hydration and biomechanics - Palma L; Marques LT; Bujan J; Rodrigues LM (Dove Medical Press, 2015)
Lídia Palma,1 Liliana Tavares Marques,1 Julia Bujan,2,3 Luís Monteiro Rodrigues1,4 1CBIOS – Research Center for Health Science and Technologies, Universidade Lusófona, Campo Grande, Lisboa, Portugal; 2Department of Medicine and Medical Specialities, Universidad de Alcalá de Henares, Madrid, Spain; 3CIBER-BBN, Madrid, España, Spain; 4Department of Pharmacological Sciences, School of Pharmacy, Universidade de Lisboa, Lisboa, Portugal Abstract: It is generally assumed that dietary water might be beneficial for the health, especially in dermatological (age preventing) terms. The present study was designed to quantify the impact of dietary water on major indicators of skin physiology. A total of 49 healthy females (mean 24.5±4.3 years) were selected and characterized in terms of their dietary daily habits, especially focused in water consumption, by a Food Frequency Questionnaire. This allowed two groups to be set – Group 1 consuming less than 3,200 mL/day (n=38), and Group 2 consuming more than 3,200 mL/day (n=11). Approximately 2 L of water were added to the daily diet of Group 2 individuals for 1 month to quantify the impact of this surplus in their skin physiology. Measurements involving epidermal superficial and deep hydration, transepidermal water loss, and several biomechanical descriptors were taken at day 0 (T0), 15 (T1), and 30 (T2) in several anatomical sites (face, upper limb, and leg). This stress test (2 L/day for 30 days) significantly modified superficial and deep skin hydration, especially in Group 1. The same impact was registered with the most relevant biomechanical descriptors. Thus, in this study, it is clear that higher water inputs in regular diet might positively impact normal skin physiology, in particular in those individuals with lower daily water consumptions. Keywords: dietary water, water consume, skin hydration, TEWL, skin biomechanics